Case study: supply chain management of cotton, and SiO 2 and TiO 2 nanoparticles - Quemba-Pachón, Loren Tatiana
The worldwide success of sports in Colombia has increased the attraction in the practice of high performance and outdoor sports, originating the need for clothing adaptable to the demanding and variable climatic conditions presented in the tropics during training. The objective of this research is to identify the supply chain of raw materials to obtain a functionalized textile with a nanotechnological coating locally and externally for the development of the SENNOVA project, functionalization of biodegradable textiles with SiO2 and TiO2 nanoparticles for sports apparel. For the development of the supply chain, five phases were taken into account: planning, sourcing, manufacturing, delivery and logistics, and finally return. The results of the research show that, in Colombia, Bogota is not producing technological development in textile garments using nanoparticles to confer properties to the fabrics, it was found that most of the companies import this type of garments.